Development of digital storytelling video media to improve students' critical thinking and communication skills on environmental change material - Natasya N; Abdul Razak; Muhyiatul Fadillah; Reki Kardiman (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This research is a research and development study of learning media based on Digital Storytelling (DS) on environmental change material to improve students' critical thinking and communication skills. Using the 4-D model (Define, Design, Develop, Disseminate) combined with a quasi-experimental design (quasi-experimental pretest-posttest control group design) with an intervention duration of 3 meetings, this study applied a purposive sampling technique involving 48 eleventh-grade students divided into an experimental group (n=24) and a control group (n=24). The results showed that the media was highly valid (97.31%) and highly practical based on teacher perception (92.11%) and student perception (92.71%). Data collection for critical thinking skills used a standardized test (α = 0.90). The effectiveness test using an independent samples t-test showed a statistically significant increase in critical thinking skills, where the experimental class achieved an average N-Gain score of 83.98% (high category) compared to the control class which only obtained 48.69% (p = 0.000). In addition, students' communication skills in the experimental group increased significantly based on the Mann-Whitney U test (p = 0.000) with a large effect size (r = 0.862). In conclusion, the Digital Storytelling video media proved to be valid, practical, and highly effective in improving students' critical thinking and communication skills on environmental change material.